2020
DOI: 10.1186/s41239-020-00187-1
|View full text |Cite
|
Sign up to set email alerts
|

The benefits and caveats of using clickstream data to understand student self-regulatory behaviors: opening the black box of learning processes

Abstract: Student clickstream data-time-stamped records of click events in online courses-can provide fine-grained information about student learning. Such data enable researchers and instructors to collect information at scale about how each student navigates through and interacts with online education resources, potentially enabling objective and rich insight into the learning experience beyond self-reports and intermittent assessments. Yet, analyses of these data often require advanced analytic techniques, as they on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 64 publications
1
49
0
Order By: Relevance
“…There are several reasons that might explain the non-significant findings. First of all, although clickstream data enable researchers to gather fine-grained information about students' interactions with the device, concerns have been raised that this data source only provides a partial and noisy record of a student's actions (Baker et al, 2020). Also, during the intervention, we found that some page loading errors occured to some students while they were reading the WKe-Book.…”
Section: Non-significant Findings For the Time And Frequency-related Log Variablesmentioning
confidence: 93%
“…There are several reasons that might explain the non-significant findings. First of all, although clickstream data enable researchers to gather fine-grained information about students' interactions with the device, concerns have been raised that this data source only provides a partial and noisy record of a student's actions (Baker et al, 2020). Also, during the intervention, we found that some page loading errors occured to some students while they were reading the WKe-Book.…”
Section: Non-significant Findings For the Time And Frequency-related Log Variablesmentioning
confidence: 93%
“…• Navigation time was computed as the cumulative time, in minutes, between web browser navigation events in the LMS, excluding any measured durations between navigation events greater than or equal to 25 minutes (which were likely to be periods of inactivity), and excluding durations between web browser sessions (Baker et al, 2020).…”
Section: Learning Management System (Lms) Recordsmentioning
confidence: 99%
“…One promising method for understanding SRL in online learning is to observe students' behaviors within a course's Learning Management System (LMS) [5,26,37]. Some LMS services allow researchers to obtain student clickstream data, which are timestamped logs that record every single click event in the course, such as the specific page or resource a student visited.…”
Section: Introductionmentioning
confidence: 99%
“…Some LMS services allow researchers to obtain student clickstream data, which are timestamped logs that record every single click event in the course, such as the specific page or resource a student visited. A large online course of about 300 students can produce roughly 380,000 individual data points [5]. Because of the size and richness of the data, researchers have been able to take advantage of data mining techniques to develop sophisticated models of college student learning [16,23].…”
Section: Introductionmentioning
confidence: 99%